Chirurgiczne leczenie nieprawidłowych pęcherzyków filtracyjnych u dzieci i młodzieży - Klimczak-Ślączka, Dorota; Grałek, Mirosława; Chipczyńska, Barbara; Kanigowska, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The aim of this paper is to present our own experience in the treatment of cystic blebs in children and young adults. This complication, which is the most popular after trabeculectomy with antimetabolic agents, can be the reason of late endophthalmitis. Surgical treatment is one of the method to prewent it. In the study 6 patients with cystic blebs after trabeculectomy with mitomycin C was presented. 4 of them was treated surgicaly. We described the method of surgery and the results.